Konieczność przestrzegania „normy personalistycznej" w społeczeństwie informacyjnym - Jędraszewski, Marek (Wydział Teologiczny UAM, 2009)
Necessity of complying with personalistic norms in the information society „Information society” which is arising now, is becoming a huge cultural and civilization challenge. To avoid threats to this group, which are appearing with more force, personalistic norms must be brought back to the members of this society. Karol Wojty3a touched upon this subject in his books: Love and Responsibility (1960) and The Acting Person (1969). He wrote about being fulfilled as a human being trough the act and about authentic and nonauthentic social attitudes.
The Necessity to Obey the „Personalistic Norm" in an Information Society
Keywords: personalistic norm; solidarity; opposition; truth